2017
DOI: 10.1111/cei.12951
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to box A of high mobility group box 1 in systemic lupus erythematosus

Abstract: Autoantibodies to nuclear structures are a hallmark of systemic lupus erythematosus (SLE), including autoantibodies to nuclear protein high mobility group box 1 (HMGB1). HMGB1 consists of three separate domains: box A, box B and an acidic tail. Recombinant box A acts as a competitive antagonist for HMGB1 and might be an interesting treatment option in SLE. However, antibodies to box A might interfere. Therefore, levels of anti-box A were examined in SLE patients in association with disease activity and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…35 The amount of HMGB1 in SLE serum is increased compared with healthy controls 36 ; however, the HMGB1 enzyme-linked immunosorbent assay is an inadequate instrument for measuring HMGB1 levels in active SLE patients. 17 Therefore, we chose to use a saturating concentration of HMGB1 (3 mg/mL) and C1q levels up to 50 ug/mL. As anticipated, the addition of HMGB1 dramatically increased the transcription and secretion of type 1 IFN, IFN-inducible genes, and NFkB-dependent proinflammatory cytokines, as previously reported 7 ( Figure 1A-B).…”
Section: C1q Inhibits Hmgb1-induced Monocyte Activationmentioning
confidence: 75%
See 2 more Smart Citations
“…35 The amount of HMGB1 in SLE serum is increased compared with healthy controls 36 ; however, the HMGB1 enzyme-linked immunosorbent assay is an inadequate instrument for measuring HMGB1 levels in active SLE patients. 17 Therefore, we chose to use a saturating concentration of HMGB1 (3 mg/mL) and C1q levels up to 50 ug/mL. As anticipated, the addition of HMGB1 dramatically increased the transcription and secretion of type 1 IFN, IFN-inducible genes, and NFkB-dependent proinflammatory cytokines, as previously reported 7 ( Figure 1A-B).…”
Section: C1q Inhibits Hmgb1-induced Monocyte Activationmentioning
confidence: 75%
“…11,17 Because C1q inhibited HMGB1-induced cytokine secretion, we asked whether this might result from a C1q-mediated inhibition of the internalization of HMGB1. We incubated AF555-HMGB1-labeled HMGB1 with freshly isolated monocytes in the presence or absence of C1q and performed imaging flow cytometry.…”
Section: C1q Inhibits Hmgb1 Internalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although serum levels of HMGB1 have been associated with disease activity and LN features, 15,17 previous studies using ELISA to determine the serum levels of HMGB1, 24 have demonstrated that the performance of this method is limited 10 because of the union of extracellular HMGB1 to free DNA 37 and the high prevalence of anti-HMGB1 autoantibodies in SLE patients. 22,38 In contrast, when HMGB1 was quantified by Western blot, the serum levels were higher in patients with renal involvement. 16,24,39 The discordant results are explained by the union of extracellular HMGB1 to free DNA 37 and anti-HMGB1 autoantibodies, frequently present in SLE patients, 22,38 which affect the ELISA performance.…”
Section: Discussionmentioning
confidence: 97%
“…HMGB1 is a nuclear protein capable of binding to DNA, thereby regulating gene transcription, chromatin replication and DNA repair [40]. HMGB1 consists of three domains; A box, B box, and an acidic tail.…”
Section: Hmgb1mentioning
confidence: 99%